Impact of an integrative activity based on clinical practices on the teaching of basic and health care pharmacology curriculum to pharmacy students - Francisco A. FARIAS-FILHO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objective: The aim of this work was to evaluate the impact of an integrative activity based on clinical practices in disciplines of the basic and health care curriculum of an undergraduate pharmacy school. Methods: We developed an applied an interdisciplinary methodology in basic and health care disciplines focused on hospital pharmacy practice, including Pharmacokinetics and Pharmacodynamics; Hospital Pharmacy; Pharmacology I; Pharmacology II; Toxicology; Clinical Pharmacy. The methodology used was constructed on problem-based learning (PBL) focused on the health policies integrated into pharmaceutical clinical practices. Students were encouraged to formulate hypotheses, plan experiments and to discuss their outcomes. The evaluation of the effectiveness of the methodology was performed by analyzing the following parameters: escaping of discipline and measurement of students' performance improvement. Results: We noted that students were able to reformulate their original perceptions immediately after teaching. The students significantly reduced the avoidance of Pharmacology I; Pharmacology II; Toxicology. Furthermore, the students significantly improved their school performance in all disciplines with the exception of Pharmacology I; Pharmacokinetics and Pharmacodynamics. Conclusion: The use of the integrative methodology based on clinical practice resulted in lower dropout and better academic performance. In addition, the use of this methodology promoted greater integration of students in the health care problems and clinical practices.